Muscular Dynamic Reeducation in Postural Balance and in lumbar pain reduction for industry workers - Francisco Miguel Pinto; Elirez Bezerra da Silva; José Knoplich; Silvia Correa Bacelar; Guilherme Bertoni; Estélio Henrique Martin Dantas (O Mundo da Saúde, 2010)
The objective of this study has been to investigate the effect of the Muscular Dynamic Reeducation in Postural Balance and in lumbar pain reduction for industry workers. The sample has been constituted by lumbago-affected industry operators assisted by the sector of Physiotherapy. Using inclusion and exclusion criteria, 82 individuals randomly included in two groups: experimental group (EG; n = 41, age = 41±4 years; body mass index (BMI) = 26.46±3.25) and control group (CG; n = 42; age = 42±5 years; BMI = 26.47±3.34). EG has participated in a treatment using RDM. GC was constituted by individuals that have not participated in any physiotherapeutic treatment during the research. The procedures used for the evaluation were lumbago (Borg scale) and postural balance (stabilometric and posturometric platform). RDM intervention procedure lasted 20 minutes, twice a week, during 12 weeks, and the treatment was used in 4 different moments. Intragroup comparison, paired t test or Wilcoxon presented, respectively, a significant improvement (p < 0.05) in the variables lumbar pain (p = 0.0001) and postural balance (p = 0.0001) in EG. Kruskal Wallis test, followed through the confidence interval (CC), showed significant improvements of EG in the post-test compared to CG in post-test (lumbar pain: IC: - 115.58/-48.6; postural balance: IC: -68.81/-1.89). In addition, Chi-square test showed a significant reduction in drug use by EG in both intragroup (p = 0.0001) and intergroup (p = 0.0001) analysis. We may then infer that the treatment with RDM has produced a significant improvement of lumbar pain and postural balance of industry operators.